The Peculiarities of Parent-Child Relationship among Teenagers who are Addicted to Online Games - Eliseeva M.I.; Krieger E.E. (Психолого-педагогические исследования)
The family is one of the main institutions for raising a child, starting from the moment of birth and ending with his formation of a mature personality. The development of parent-child relations will determine the further formation of a person, including the emergence of addictions and other deviations. This article is devoted to the problem of the relationship between parents among teenagers who are addicted to online games. The sample consisted of 50 people, including students of secondary schools, public colleges and technical schools. Among them there are 21 girls and 29 boys aged 14 to 18 years. In the course of the study, test methods: PVP Questionnaire (Problem Video Game Playing Questionnaire) of Dr. Ricardo Tejeiro-Salguero and Dr. Rosa María Bersabé-Moran (designed to measure the disorder commonly referred to as video game addiction); questionnaire PCI (parent-child interaction) of I.M. Markovskaya. In the course of the study, a relationship was established between the assessment of satisfaction with relationships with parents and with the degree of dependence on video games in complete and single-parent families. The results showed that adolescents who are addicted to online games can experience disharmonious relationships with both their mother and father. It was found that the assessment of satisfaction with relations with parents does not depend on the composition of the family. The results also demonstrated the presence of violations in the structure of parent-child relations, which contribute to the escape from reality in online games in order to compensate for those needs that parents could not realize.